Marketing Strategies in Entrepreneurship – A Case Study of WhiteHat Jr - Saini, Ramandeep (Indian Journal of Marketing, 2022)
The case outlined the roller coaster ride of the startup, WhiteHat Jr, from its inception in November 2018 till February 2021. The edutech organization was founded in Mumbai in India and, within no time, accelerated its growth. The app developed by the company taught the kids falling in the age group of 6–18 years how to develop animations, commercial games, and online apps by applying the basics of coding. By October 2019, the company managed to grow substantially and had 500 teachers while achieving 100% student and revenue growth every next month. August 2020 saw the acquisition of WhiteHat Jr by Byju’s, and all was finalized in six weeks, and the papers were signed virtually. This was followed by an aggressive advertisement campaign, but it didn’t go well with users. The company started making efforts to improve its reputation, and by December 2020, it decided to stop the controversial ads. In an interview, the founder of WhiteHat Jr, Karan Bajaj, admitted that the company should not have emphasized employability for young kids in its advertisements. The challenge ahead for the company is to develop strategies for damage control, future growth, and expansion.